Rancang Bangun Timbangan Digital Dengan Keluaran Berat Berbasis Arduino Uno Pada Automatic Machine Measurement Mass And Dimension - Muflihana, Afdila; Arief, Dodi Sofyan; Nugraha, Aditya Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The logistics packages sent consist of various types of sizes and weights, so shipping costs are determined by the weight and size or dimensions of the goods. Almost all logistics companies in Indonesia still use conventional and separate methods in determining the volume and weight of logistics packages that play a role in determining prices, namely by measuring the dimensions of logistics packages using meters to obtain volume and then measuring the weight using the scales. To overcome the above, the idea was to create an Automatic Bulk Measurement and Dimension Machine that can process volume and weight measurements automatically at the same time making it more efficient. In relation to mass measurement, researchers will design devices related to mass or commonly called digital scales that use load cells with a capacity of 50 kg. Other supporting components are the Arduino Uno and HX711 modules as input signal amplifiers, where the analog data obtained will be received by the ADC which will be converted into digital data. Digital data will be processed again by the Arduino programming language to display the results on the LCD in units of gram (gr). Based on testing, with the same variation in load placement, the best position of the load is obtained when measuring mass, which is in the middle of the base with a percentage level (%). And the measurement results by varying the nominal load at the same interval where the load is placed in the middle of the base, then the percentage level (%) is obtained with an error of 0.032% and the percentage success rate of tool measurement is 99.968%. This shows the mass measurement process using a well-designed tool. Keyword: Digital Scale, Load cell, HX711, Arduino, LCD